Programa ACT: avaliação de uma intervenção com profissionais para prevenção universal da violência contra crianças - Pontes, Luciana Barbalho (Universidade Federal de São Carlos, 2020)
The Brazilian “Boy Bernardo” law provides for the elaboration of public policies and the implementation of actions such as professional training programs, in order to prevent the use of physical punishment and to spread positive parenting practices. The first chapter of this thesis discusses that law as an agent of cultural change in Brazil. Professional training on the ACT Program fits perfectly into the scope of the law, as it aims to teach parents and professionals about the consequences of violence, child development, anger management and positive parenting strategies and thus contribute to child abuse prevention. Chapters 2 and 3 aim to evaluate a 21-hour ACT Facilitator Training Workshop through a feasibility and a quasi-experimental study, with pre-test, post-test and one-month follow-up measures. Finally, chapter 4 presents a qualitative evaluation of the program dissemination after two years. As a result, in both quantitative studies, participants significantly increased their knowledge on child development over time, but there were no significant differences regarding their child abuse potential score. The feasibility study also obtained increased knowledge on parenting styles and reduced levels of rigidity after training. The quasi-experimental study found no difference between groups, but it did significantly reduce levels of distress and increase ego-strength levels of professionals over time. Although the rate of program dissemination in the study was zero, the informal dissemination of its content and its integration into their professional practice occurred. Therefore, the ACT Training Workshop proved to be effective in increasing and disseminating knowledge related to violence prevention. However, adjustments are necessary to make the train-the-trainer model and the evaluation of program dissemination work successfully in order to achieve a large-scale implementation of the ACT Program as a public policy in Brazil, in compliance with the law.
ACT Program: evaluation of an intervention with professionals for child abuse universal prevention
Keywords: Violência contra a criança; Prevenção; Capacitação profissional; Avaliação; Child abuse; Prevention; Professional training; Evaluation; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA